Pengaruh Kompetensi, Akuntabilitas, Pengendalian Internal dan Partisipasi Masyarakat Terhadap Efektivitas Pengelolaan Dana Desa Kebonagung Malang - Ratieh Aldela Megaayu I; Dwiyani Sudaryanti; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to explain the influence of competence, accountability, internal control and community participation on the effectiveness of village fund management in Kebonagung Malang. This research uses quantitative research methods. The data analysis method used is multiple linear regression analysis. Sources of data in this study were primary data using questionnaires and assessed with a Likert scale obtained from Kebonagung Malang Village apparatus, totaling 40 people. Sampling was carried out using purposive sampling method. The results of this study indicate that the variables of competence, accountability, internal control and community participation have a positive effect on the effectiveness of managing village funds.Keywords: Competence, accountability, internal control, community participation, effectiveness of village fund management